Development of an Operative Trauma Course in Ugandad - A Report of a Three-Year Experience - Ullrich, Sarah J.; DeWane, Michael P.; Cheung, Maija; Fleming, Matthew; Namugga, Martha M.; Kurigamba, Gideon; Kabuye, Ronald; Mabweijano, Jackie; Galukande, Moses; Ozgediz, Doruk; Pei, Kevin Y. (Journal of Surgical Research, 2020)
Trauma is a leading cause of morbidity and mortality in low-income countries. Improved health care systems and training are potential avenues to combat this burden. We detail a collaborative and context-specific operative trauma course taught to postgraduate surgical trainees practicing in a low-resource setting and examine its effect on resident practice. Three classes of second year surgical residents participated in trainings from 2017 to 2019. The course was developed and taught in conjunction with local faculty. The most recent cohort logged cases before and after the course to assess resources used during initial patient evaluation and operative techniques used if the patient was taken to theater. Over the study period, 52 residents participated in the course. Eighteen participated in the case log study and logged 117 cases. There was no statistically significant difference in patient demographics or injury severity precourse and postcourse. Postcourse, penetrating injuries were reported less frequently (40 to 21% P < 0.05) and road traffic crashes were reported more frequently (39 to 60%, P < 0.05). There was no change in the use of bedside interventions or diagnostic imaging, besides head CT. Of patients taken for a laparotomy, there was a nonstatistically significant increase in the use of four-quadrant packing 3.4 to 21.7%) and a decrease in liver repair (20.7 to 4.3%). The course did not change resource utilization; however, it did influence clinical decision-making and operative techniques used during laparotomy. Additional research is indicated to evaluate sustained changes in practice patterns and clinical outcomes after operative skills training.
Keywords: Development; Operative Trauma Course